A cluster randomised controlled trial of a secondary school intervention to reduce intake of sugar‐sweetened beverages: Mid‐intervention impact of switchURsip environmental strategies. (5th March 2021) - Sutherland, Rachel; Ying Ooi, Jia; Finch, Meghan; Yoong, Sze Lin; Nathan, Nicole; Wrigley, Jessica; Reilly, Kathryn; Janssen, Lisa; Wiggers, John; Wolfenden, Luke
Abstract: Issue addressed: Secondary schools provide an opportune setting for interventions addressing excessive sugar‐sweetened beverage (SSB) intake in adolescence. This trial aimed to assess the impact of school environmental strategies, delivered as part of a broader intervention, among Year 7‐9 students' SSB consumption. Methods: Between March and July 2018, we conducted a cluster randomised controlled trial with 862 students attending six secondary schools (3 intervention and 3 control) in New South Wales. The intervention targeted SSB availability, placement, promotion and pricing, and increased availability and promotion of water. Control schools followed their usual programmes. Primary outcomes included mean daily SSB consumption (millilitres) and mean daily percentage energy from SSB (kilojoules). Sub‐group analysis explored primary outcomes for gender, school year level and frequency of canteen use. Results: Of the 2265 eligible students, 1092 (50.2%) provided active parental consent and 940 (86.0%) participated in baseline data collection. No significant differences were observed between groups at follow‐up for mean daily SSBs consumed (−10.17 mL, CI: −24.78; 45.12, P  = 0.57) or mean daily percentage energy from SSBs (−0.20%, CI: −0.87; 0.47, P  = .56). Significant effects were observed among girls in intervention compared to girls in control schools for mean daily SSB consumption (−52.02 mL, CI 99.8; 94.14, P  = .03) and mean daily percentage of energy from SSBs (−0.90%, CI: −1.82; 0.02, P  = .05). Conclusions: At 3‐month mid‐intervention evaluation, the intervention failed to impact on mean daily consumption and mean percentage energy from SSBs, overall. However, an intervention effect was observed in girls. The limited overall effect is likely due to inadequate intervention dose related to the short duration, limiting opportunities for schools to fully implement the environmental strategies. So what?: A longer intervention duration with additional implementation support to allow adequate time to embed the strategies within the school is recommended. Implementation support strategies would ensure staff are supported throughout the process.